Relationships Between Distention-, Butyrate- and Pellet-Induced Stimulation of Peristalsis in the Mouse Colon - Tan, Wei; Lee, Grace; Chen, Ji-Hong; Huizinga, Jan D. (Frontiers in Physiology, 2020)
Background/Aims Luminal factors such as short-chain fatty acids are increasingly recognized for playing a regulatory role in peristaltic activity. Our objective was to understand the roles of butyrate and propionate in regulating peristaltic activity in relation to distention-induced activities. Methods Butyrate and propionate were perfused intraluminally under varying intraluminal pressures in murine colons bathed in Krebs solution. We used video recording and spatiotemporal maps to examine peristalsis induced by the intrinsic rhythmic colonic motor complex (CMC) as well as pellet-induced peristaltic reflex movements. Results The CMC showed several configurations at different levels of excitation, culminating in long distance contractions (LDCs) which possess a triangular shape in murine colon spatiotemporal maps. Butyrate increased the frequency of CMCs but was a much weaker stimulus than distention and only contributed to significant changes under low distention. Propionate inhibited CMCs by decreasing either their amplitudes or frequencies, but only in low distention conditions. Butyrate did not consistently counteract propionate-induced inhibition likely due to the multiple and distinct mechanisms of action for these signaling molecules in the lumen. Pellet movement occurred through ongoing CMCs as well as pellet induced peristaltic reflex movements and butyrate augmented both types of peristaltic motor patterns to decrease the amount of time required to expel each pellet. Conclusions Butyrate is effective in promoting peristalsis, but only when the level of colonic activity is low such as under conditions of low intraluminal pressure. This suggests that it may play a significant role in patients with poor fiber intake, where there is low mechanical stimulation in the lumen.